ENT 530 Social Media Portfolio : Choce Jar/ Misshirley Manan - Manan, Misshirley (2019)
For the entrepreneur project business, I had choose to sell food product which is chocolate rice as in Choco Rice Jar. This food product more into junk food but some does said that it is also a kind of dessert food. This where the raw materials of the food are chocolate and bubble rice. It's call as Choco Rice Jar since its a mixture of chocolate and bubble rice in a glass jar.